Interventions for primary prevention of cardiovascular disease: umbrella review of systematic reviews - Olalekan A Uthman; Lena Al-Khudairy; Chidozie Nduka; Rachel Court; Jodie Enderby; Seun Anjorin; Hema Mistry; G J Melendez-Torres; Sian Taylor-Phillips; Aileen Clarke (Health Technology Assessment, 2024)
Background Cardiovascular diseases are the leading cause of death globally. The aim of this overview of systematic reviews was to compare the effectiveness of different pharmacological and non-pharmacological interventions for the primary prevention of cardiovascular disease. Methods A structured search of the Cochrane Database of Systematic Reviews, MEDLINE, EMBASE and the Database of Abstracts of Reviews of Effects archive was conducted to find systematic reviews that reported the effect of various pharmacological and non-pharmacological interventions for the primary prevention of cardiovascular disease from inception to March 2021. References of included studies were also checked. The included systematic reviews’ methodological quality was assessed using the Assessment of Multiple Systematic Reviews 2 instrument (range, 0–16). The outcomes of each included review’s meta-analysis were extracted and described narratively. Results This study analysed 95 systematic reviews, including 41 on non-pharmacological interventions and 54 on pharmacological interventions for cardiovascular health. The majority of the reviews focused on lipid-lowering interventions (n = 25) and antiplatelet medications (n = 21), followed by nutritional supplements, dietary interventions, physical activity, health promotion and other interventions. Only 1 of the 10 reviews addressing cardiovascular mortality showed a potential benefit, while the others found no effect. Antiplatelets were found to have a beneficial effect on all-cause mortality in 2 out of 12 meta-analyses and on major cardiovascular disease events in 8 out of 17 reviews. Lipid-lowering interventions showed beneficial effects on cardiovascular disease mortality, all-cause mortality and major cardiovascular disease events in varying numbers of the reviews. Glucose-lowering medications demonstrated significant benefits for major cardiovascular events, coronary heart disease events and mortality. However, the combination of dietary interventions, physical activities, nutritional supplements and polypills showed little or no significant benefit for major cardiovascular outcomes or mortality. Future work and limitations More research is needed to determine whether the effect of treatment varies depending on population characteristics. The findings of this review should be interpreted with caution because the majority of studies of non-pharmacological interventions compare primary prevention with usual care, which may include recommended pharmacological treatment in higher-risk patients (e.g. statins and/or antihypertensive medications, etc.). In addition, randomised controlled trial evidence may be better suited to the study of pharmacological interventions than dietary and lifestyle interventions. Conclusions This umbrella review captured the variability in different interventions on randomised controlled trial evidence on interventions for primary prevention of cardiovascular disease and identified areas that may benefit from further research. Specifically, this review focused on randomised controlled trial evidence on interventions for primary prevention of cardiovascular disease. Researchers may use these findings as a resource to direct new intervention studies and network meta-analyses to compare the efficacy of various interventions based on these findings. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment (HTA) programme as award number 17/148/05. Plain language summary Heart and blood vessel diseases are the top cause of death worldwide. This study aimed to compare the effectiveness of various drug-based and non-drug-based methods in preventing these diseases. We searched databases like Cochrane, MEDLINE, EMBASE and the Database of Abstracts of Reviews of Effects archive to find reviews about different ways to prevent heart and blood vessel diseases up until March 2021. The results showed that only 1 out of 10 reviews found a possible benefit in reducing heart-related deaths, while the other 9 found no effect. Medicines that lower blood sugar levels had a positive impact on reducing major heart events, heart disease and death. However, combining dietary changes, exercise, nutritional supplements and polypills had little or no effect on reducing heart-related events, deaths due to heart disease or deaths from all causes. This review examined the available evidence on ways to prevent heart and blood vessel diseases and identified areas where more research could be beneficial. Future studies could compare the effectiveness of different interventions using new methods and analyses.